Ancestral Spirits: Influence on the Way of Life of the Thai Yuan-Lanna Ethnic Group: Ancestral Spirits: Influence on the Way of Life of the Thai Yuan-Lanna Ethnic Group - Mulaseewa, Phathairat; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic article aims to present the ancestral spirits that influence the way of life of the Thai Yuan-Lanna ethnic group. The result of this studies reveals that the ancestral spirits have influenced the way of life of the Thai Yuan-Lanna ethnic group in 4 aspects as follows. 1) Philosophy and Belief: it is a characteristic of a way of life that arises from beliefs that have been passed down from ancestors and practiced until becoming rules and cultural ways of society. For example, beliefs about gratitude children have for their parents and grandparents. 2) Art: it has been reflected in the murals of the Buddhist temples including literature, legends and folk tales. 3) Culture: it is reflected in the form of language, writing and food consumption and 4) Tradition: it causes the tradition to ask for rain, Song-Puthean-Yathean Tradition, Poi Tradition and Songkran Tradition etc.